Comparison of Outpatient Foley Bulb Induction to Traditional Induction of Labor [18J]. (May 2018) - Bull, Mary; Hong, Christina; Roth, Patrick; Washburn, Mark
Abstract : INTRODUCTION: More than 20% of pregnant women in the U.S. undergo induction. Due to an unfavorable cervix, many of the women presenting for induction experience longer labor times, increased rates of cesarean section and increased healthcare costs. The purpose of the study was to examine the difference in cesarean section rates, maternal and neonatal morbidity and costs for outpatient vs inpatient Foley induction. METHODS: We conducted a retrospective case control study using data from the Kaiser Permanente electronic medical record for the Orange County Service area. Cases were identified using a log of all patients receiving Foley bulb placement. Controls were identified through the electronic health record using Current Procedural Terminology codes and International Classification of Diseases 9th Revision codes for induction of labor from 2013-2015. Cases and controls were matched by advanced maternal age status, parity and race. Patients were excluded if they had a modified bishop score >6 or nonvertex presentation or <37 weeks gestation. RESULTS: Between 9/2013 and 12/2015, 283 cases were identified and matched 1:1 to controls. There was no difference between cases and controls for rate of cesarean (P>0.89) or for maternal (P>0.37) or neonatal morbidity (P<0.5). Cases were more likely to have an infant with a higher birth weight (P<0.01), have a shorter length of hospitalization for labor and delivery (P<0.01) and lower costs of hospitalization (P<0.01). Cost was quantified, with average 300 dollars per patient savings for outpatient induction. CONCLUSION: Outpatient Foley bulb placement is a safe, cost effective alternative for women undergoing induction of labor.